2017
DOI: 10.1037/xge0000306
|View full text |Cite
|
Sign up to set email alerts
|

Impact bias or underestimation? Outcome specifications predict the direction of affective forecasting errors.

Abstract: Affective forecasts are used to anticipate the hedonic impact of future events and decide which events to pursue or avoid. We propose that because affective forecasters are more sensitive to outcome specifications of events than experiencers, the outcome specification values of an event, such as its duration, magnitude, probability, and psychological distance, can be used to predict the direction of affective forecasting errors: whether affective forecasters will overestimate or underestimate its hedonic impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 71 publications
(206 reference statements)
2
37
0
Order By: Relevance
“…Predictions diverge most from experience when they encompass emotion duration or mood. Changing appraisals of events, and attending to salient but unrepresentative features of events, can result in either over-or underestimating emotion [25,26,28]. Consistent with evidence that common cognitive processes underlie prospection and retrospection, similar patterns of accuracy and bias, and similar sources of bias, are found when people predict and remember emotion.…”
Section: Asymmetries Between Predicting and Remembering Emotionsupporting
confidence: 56%
See 1 more Smart Citation
“…Predictions diverge most from experience when they encompass emotion duration or mood. Changing appraisals of events, and attending to salient but unrepresentative features of events, can result in either over-or underestimating emotion [25,26,28]. Consistent with evidence that common cognitive processes underlie prospection and retrospection, similar patterns of accuracy and bias, and similar sources of bias, are found when people predict and remember emotion.…”
Section: Asymmetries Between Predicting and Remembering Emotionsupporting
confidence: 56%
“…Recent research reveals underestimation [26][27][28], and accuracy [12,29,30], as well as overestimation [31][32][33]. To account for this variation, Buechel, Zhang, and Morewedge [26] proposed that emotional experiences are more attention absorbing and richly detailed than forecasts. As a result, forecasters attend more than experiencers to characteristics of events that are typically diagnostic of an event's hedonic impact.…”
Section: Similar Sources and Patterns Of Bias When Predicting And Remmentioning
confidence: 99%
“…By systematically manipulating the level of arousal potential for the same sensory stimulus, the present research provides important insight into when and why errors in predicted liking are more or less likely to occur. This focus on how characteristics of sensory stimuli determine forecasting errors complements and extends related efforts in the affective forecasting literature in the non-sensory domain, which has examined how characteristics of events (e.g., their probability or psychological distance) differently influence their emotional impact in prospect and experience (e.g., Buechel et al 2014;Buechel, Morewedge, and Zhang 2017;Ebert and Meyvis 2014).…”
Section: Theoretical Contributionsmentioning
confidence: 83%
“…Most existing work on predicted and experienced hedonic value has focused on stimuli in the non-sensory domain. Specifically, research on affective forecasting suggests that in many cases, people overestimate how much and for how long products, events, and circumstances will impact their happiness and well-being (for overviews see Gilbert 2003, 2005;Buechel, Morewedge, and Zhang 2017). Research in this area has uncovered several sources for this forecasting error.…”
Section: Dynamics Of Hedonic Valuementioning
confidence: 99%
“…Attempting to reconcile previous findings, a recent study showed that differences in outcome specification can predict the direction of forecasting errors (Buechel, Zhang, & Morewedge, 2017).…”
Section: Discussionmentioning
confidence: 98%